Are International Students Cash Cows? Examining the Relationship Between New International Undergraduate Enrollments and Institutional Revenue at Public Colleges and Universities in the US - Cantwell, Brendan (Journal of International Students, 2015)
There has been growing interest in the business of international education. It is often assumed that universities seek international students as a means of generating revenue. The broad purpose of this study was to understand the effects of increased international student enrollment on net tuition revenue. Informed by resource dependency and academic capitalism theory, this study used panel regression techniques to estimate the effect of enrolling an international undergraduate student on tuition revenue among public colleges and universities in the United States Findings show some but not all institutions are able to generate additional income by enrolling additional international students.